2021
DOI: 10.5114/aoms/127085
|View full text |Cite
|
Sign up to set email alerts
|

The role of tensins in malignant neoplasms

Abstract: Tensins belong to the family of adhesion proteins which form focal adhesions serving as a bridge between the extracellular matrix and intracellular actin skeleton. The tensin family consists of four members (tensin-1 to -4) which are widely expressed in normal and cancerous tissues. The presence of Src homology 2 and phosphotyrosine binding domains is a unique feature of tensins which enables them to interact with tyrosine-phosphorylated proteins in PI3K/Akt and β-integrin/FAK signaling pathways. The tensin-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Analysis of the role of mammalian tensins in mice has revealed that while individual tensins are not essential for embryonic or tissue development, they are required to maintain the structure and function of the kidney and heart and for regeneration processes (reviewed in [13]). As for their role in tumorigenesis, this appears to be quite controversial, and tensin-and cell-type-specific, as they act sometimes as tumor suppressors and other times as tumor promoters (reviewed in [39]). Unlike mammals, Drosophila melanogaster and Caenorhabditis elegans have been proposed to possess one tensin each.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the role of mammalian tensins in mice has revealed that while individual tensins are not essential for embryonic or tissue development, they are required to maintain the structure and function of the kidney and heart and for regeneration processes (reviewed in [13]). As for their role in tumorigenesis, this appears to be quite controversial, and tensin-and cell-type-specific, as they act sometimes as tumor suppressors and other times as tumor promoters (reviewed in [39]). Unlike mammals, Drosophila melanogaster and Caenorhabditis elegans have been proposed to possess one tensin each.…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell cancer, TNS2 was shown to not correlate with metastases to nearby lymph nodes or to infiltrate to blood and lymphatic vessels [37]. Many other cell adhesion molecules, including members of the Tensin family but not TNS2, have been linked to metastatic activity in cancers [38]. However, TNS2 expression has been shown to correlate with the malignancy grade of gastric cancer, in addition to being more abundant in moderately differentiated tumors compared to poorly differentiated-or non-differentiated tumors, and correlating with peritumoral inflammation and H.pylori infection [39].…”
Section: Discussionmentioning
confidence: 99%
“…These domains are extremely important for the smooth operation of all tensins, despite some of their functions being conflicting between them. The SH2 domain plays a major role in tensin’s signaling pathways since it binds with phosphorylated proteins in their tyrosine amino acid, such as phosphoinositide 3-kinase (PI3K), focal adhesion kinase (FAK), tyrosine-protein kinase MET (MET), Crk-associated substrate (p130CAS), paxillin, epidermal growth factor receptor (EGFR), casitas B-lineage lymphoma (c-Cbl), proto-oncogene tyrosine-protein kinase (Src), and tyrosine-protein kinase receptor UFO (AXL) [ 3 , 4 , 5 , 6 ]. The PTB domain is also important for tensins since it binds with -integrin at the NPXY/F motifs and controls the signaling pathways that regulate cell adhesion and motility [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite tensins being known to localize to focal adhesions, CTEN is also found in the cytoplasm and the nucleus, and it is in these three sub-cellular localizations that CTEN exhibits its physiological functions [ 7 , 8 ]. Being positively regulated by several growth factors, including epidermal growth factor (EGF), transforming growth factor-beta 1 (TGF- β1), insulin-like growth factor 1 (IGF-1), interleukin-6 (IL-6), interleukin-13 (IL-13), and fibroblast growth factors (FGFs), CTEN is responsible for controlling multiple proteins and signaling pathways, through which CTEN regulates cell invasion, migration, adhesion, growth, metastasis, apoptosis, and epithelial to mesenchymal transition (EMT) [ 3 , 4 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Bearing that in mind, it is not surprising that CTEN is frequently reported as an oncogene in human cancers, although it was initially described as a tumor suppressor in prostate cancer, with very limited expression in normal tissues [ 1 ].…”
Section: Introductionmentioning
confidence: 99%